Philosophy and poetry : continental perspectives - Ghosh, Ranjan (Columbia University Press, 2019)
"Philosophy or Poetry?: A Continental Perspective is an exciting and innovative contribution to continental philosophy, aesthetics, and comparative literature that will have broad interest and appeal. The unique spirit with which major thinkers in the contemporary continental tradition engage with the challenge of poetry (and perhaps the arts in general) to questions both political and personal is conveyed in these essays commissioned from specialists and major thinkers in their own right--Georges Van Den Abbeele, Lutz Koepnick, Jean Michel Rabate, Francois Noudelmann, Claire Colebrook, Jean Philippe Deranty, and Bruno Bosteels, among others"--